PENERAPAN MODEL PEMBELAJARAN MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR BAHASA ARAB SISWA KELAS XI DI SEKOLAH QURAN DARUL FATTAH TAHUN PELAJARAN 2019/2020 - Sya'bani, Muhammad Zaky (STIT Darul Fattah Bandar Lampung, 2021)
This research originated from observations at the Darul Fattah Quran School class XI in the form of interviews with Arabic teachers and it is known that the results of learning Arabic students are still below the standard Minimum Completion Criteria with confidence and activeness of students are also still lacking and students often feel saturated due. In this study, researchers formulated problems, namely; How is the application of the Make a Match learning method in improving Arabic learning outcomes? and Can the application of the Make a Match learning method improve Arabic learning outcomes? While this research method is by studying class actions on students of class XI of darul Fattah Quran School. The results in this study cycle I obtained an average score of 67 with a percentage of 26.67% of students who managed to obtain grades to achieve KKM. Meanwhile, after the second cycle, there was an increase in average grades of 71.5 with a percentage of 70% of students getting grades to achieve KKM. After doing cycles I and II researchers continue to assess student learning outcomes in cycle III the goal is to ensure and more convincing student learning outcomes whether it has increased or decreased. In cycle III, the average student's grades still increased by 75.30 with a percentage of 6.05%.